2021
DOI: 10.1001/jamasurg.2020.6674
|View full text |Cite
|
Sign up to set email alerts
|

Organ Donation After Euthanasia Starting at Home Is Feasible

Abstract: To the Editor Van Reeven et al 1 state in their article that the results of donation-after-circulatory-death liver transplant after euthanasia are good and may enlarge the organ donor pool. However, they also state: "Despite some previous cases in which the coma-inducing drug was administered to the patient at home, today the complete euthanasia procedure is highly recommended to take place in the hospital." 1 This statement, making reference to an article that we published, 2 is unsubstantiated and may even b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…We screened 341 full-text reports, and from those, 121 met the inclusion criteria. From the 121 included sources, 107 sources 2–4,6,7,18–119 are reported in this manuscript responding to research subquestions v and vi (details on the division of results can be found in the upcoming sections and in Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We screened 341 full-text reports, and from those, 121 met the inclusion criteria. From the 121 included sources, 107 sources 2–4,6,7,18–119 are reported in this manuscript responding to research subquestions v and vi (details on the division of results can be found in the upcoming sections and in Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…23 Additionally, the series of medications administered for the MAiD procedure varies across institutions. 4,20,24,25,27,37,[40][41][42][43]45,48,49,52,53,56,61,63,[71][72][73]76,78,80,81 The anesthetic regimen for organ donation following MAiD usually includes the administration of a coma inducer (eg, propofol, barbiturate thiopental, sodium pentobarbital) 4,20,24,25,27,37,43,45,53,56,61,63,72,76,80 with or without sedatives (eg, midazolam, fentanyl), 4,43,45,53,63,72 and neuromuscular blockers (eg, rocoronium bromide, atracurium besylate, cistracurium besylate). 4,…”
Section: Figure 3: Clinical Pathway Of Organ Donation After Medical A...mentioning
confidence: 99%
“…Concerns have been expressed regarding the use of sedatives during mid‐procedure ODEH transport as, unlike propofol anesthesia, these do not guarantee complete loss of awareness. 88 , 118 …”
Section: Resultsmentioning
confidence: 99%
“…Concerns have been expressed regarding the use of sedatives during mid-procedure ODEH transport as, unlike propofol anesthesia, these do not guarantee complete loss of awareness. 88,118 Healthcare providers' conscientious objections are a familiar topic within MAiD care pathways, but less common in DCDD death pathways, typically performed with the less controversial withdrawal of life-sustaining therapy, and jurisdictions are developing protocols for this scenario. 59,77…”
Section: Eligibility and Safeguardsmentioning
confidence: 99%